Immunogenic properties of recombinant enzymes from bothrops ammodytoides towards the generation of neutralizing antibodies against its own venom (2019)
ABSTRACT: Bothropic venoms contain enzymes such as metalloproteases, serine-proteases, and phospholipases, which acting by themselves, or in synergism, are the cause of the envenomation symptoms and death. Here, two mRNA transcripts, one that codes for a metalloprotease and another for a serine-protease, were isolated from a Bothrops ammodytoides venom gland. The metalloprotease and serine-protease transcripts were cloned on a pCR®2.1-TOPO vector and consequently expressed in a recombinant way in E. coli (strains Origami and M15, respectively), using pQE30 vectors. The recombinant proteins were named rBamSP_1 and rBamMP_1, and they were formed by an N-terminal fusion protein of 16 amino acid residues, followed by the sequence of the mature proteins. After bacterial expression, each recombinant enzyme was recovered from inclusion bodies and treated with chaotropic agents. The experimental molecular masses for rBamSP_1 and rBamMP_1 agreed with their expected theoretical ones, and their secondary structure spectra obtained by circular dichroism were comparable to that of similar proteins. Additionally, equivalent mixtures of rBamSP_1, rBamMP_1 together with a previous reported recombinant phospholipase, rBamPLA2_1, were used to immunize rabbits to produce serum antibodies, which in turn recognized serine-proteases, metalloproteases and PLA2s from B. ammodytoides and other regional viper venoms. Finally, rabbit antibodies neutralized the 3LD50 of B. ammodytoides venom.